2017
DOI: 10.1007/s00247-017-3834-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report from the World Health Organisation Chest Radiography in Epidemiological Studies project

Abstract: Childhood pneumonia is among the leading infectious causes of mortality in children younger than 5 years of age globally. Streptococcus pneumoniae (pneumococcus) is the leading infectious cause of childhood bacterial pneumonia. The diagnosis of childhood pneumonia remains a critical epidemiological task for monitoring vaccine and treatment program effectiveness. The chest radiograph remains the most readily available and common imaging modality to assess childhood pneumonia. In 1997, the World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…Importantly, the WHO radiographic primary endpoint pneumonia does not differentiate between alveolar consolidation and atelectasis. 16,20 Overall the results from this analysis indicate that lung recordings have potential for use as a pneumonia diagnostic among children.…”
Section: Digitally Recorded Lung Sounds and Mortalitymentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, the WHO radiographic primary endpoint pneumonia does not differentiate between alveolar consolidation and atelectasis. 16,20 Overall the results from this analysis indicate that lung recordings have potential for use as a pneumonia diagnostic among children.…”
Section: Digitally Recorded Lung Sounds and Mortalitymentioning
confidence: 77%
“…19 Furthermore, radiographic equipment is expensive, facility-based, and there is a lack of interpretation expertise in most LMICs. 20 All of these issues pose barriers to wide-scale implementation of chest radiography in LMICs. Digital stethoscopes that incorporate an automated lung sound processing algorithm, on the other hand, circumvent these obstacles and have the potential to be a community-based, noninvasive point-of-care pneumonia diagnostic.…”
Section: Digitally Recorded Lung Sounds and Mortalitymentioning
confidence: 99%
“…According to the literature, current training programs have only assessed pre‐ and posttraining knowledge, not long‐term standardization . WHO developed a methodology for CXR interpretation in the epidemiological study to allow for improved diagnosis of bacterial pediatric pneumonia and generalizability of epidemiological studies . A similar consensus methodology for LUS training and standardization may allow for better application of LUS for the diagnosis of pediatric pneumonia in low‐resource settings …”
Section: Discussionmentioning
confidence: 99%
“…12 A limitation to the use of LUS in epidemiological studies of pediatric pneumonia is a lack of consensus on what constitutes a primary endpoint pneumonia and an optimal scanning protocol 13-15 ; unlike CXR, which has well-established criteria for training and interpretation. 16 Studies have shown that LUS may be able to replace CXR as an imaging modality for pneumonia 17 with no change in clinical outcomes. 18 As the use of LUS becomes more commonplace, we are left with the challenge of disseminating this skill for further research and clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinicians and radiologists are involved in making the diagnosis of pneumonia, and these groups need clarity on their respective roles. Mahommed and colleagues [2] describe one environment where clinicians and radiologists are engaging in discussions through the World Health Organization Chest Radiography in Epidemiological Studies project and where definitions of chest radiograph findings representing pneumonia are being revised for vaccine trials. This process has come about because of criticism and dissatisfaction with the previous radiographic World Health Organization definitions for pneumonia.…”
mentioning
confidence: 99%